Agreements on Individual Accounts using Guarantee of Certificate which Bound by Selling Deed - Heni Astuti; Bambang Tri Bawono (Sultan Agung Notary Law Review, 2021)
In ancient times it was customary for people to make loan agreements involving land. Land is also commonly loaned to other people under a lease agreement. In Indonesia, lending and borrowing agreements are regulated in Article 1754 of the Civil Code concerning debts and receivables. Accounts payable begins with an agreement between two legal subjects called debtors and creditors, then accompanied by the delivery of objects as collateral. Today, in the Limbangan sub-district, Kendal regency, Central Java, there is a practice of individual debt agreements with guaranteed land and building certificates with an area of 255 m² which are bound not by a Mortgage Deed (APHT), but using a Sale and Purchase Deed (AJB) and legalized by a Notary as Land Deed Maker Official (PPAT). The purpose of this study was to determine and analyze the validity of an individual debt agreement using a certificate guarantee bound by a Sale and Purchase Deed in Kendal regency. Another objective is to find out and analyze the responsibilities of a Notary to the making and registration of a Sale and Purchase Deed which is used as a guarantee for an individual debt agreement in Kendal regency. This study uses a research method in the form of Sociological Juridical which is also called field research. According to its nature, the research to be conducted has a descriptive analytical research type. The type of data used is primary data and secondary data, and data collection tools used are field studies and literature studies. Based on the discussion discussed in this study and the data that has been collected that the validity of the guarantee of property rights to land bound using a deed of sale and purchase in Kendal regency is legal and can be carried out according to legal certainty theory, as long as the main agreement of the guarantee is not Contrary to the provisions stipulated in Article 1320 of the Civil Code regarding the legal terms of the agreement, namely agreement, competence, a certain matter and a lawful cause. The powers and responsibilities of a notary in Kendal regency are in accordance with the theory of authority that has been described, namely attributive authority, delegative authority, and mandate authority and in carrying out his position to make and register the sale and purchase deed has been meticulous and thorough as mandated by article 16 paragraph (1) UUJN. However, the notary should still propose a guarantee agreement on land and buildings tied using mortgage rights not with a sale and purchase deed so that unwanted things do not happen that can harm both parties even though in fact the duties or responsibilities of the notary are basically not responsible for the contents. The deed made before him because the contents of the deed are the will and agreement desired by the parties.